Falsafah Dan Hikmah Asuransi Syariah Dalam Perspektif Nilai Dan Masaqid Al-Syari’ah - Maulida Nurhilaly; Siti Maryam; Kurniati Kurniati (CV. ITTC INDONESIA, 2025)
This study aims to analyze the philosophy and wisdom of Islamic insurance (takaful) from the perspective of values and maqāṣid al-syarī‘ah as the normative and philosophical foundation of the Islamic financial system. Using a descriptive qualitative approach through library research, this study examines academic literature and scholarly journal articles published between 2020 and 2025. The findings reveal that Islamic insurance serves as a practical manifestation of maqāṣid al-syarī‘ah, particularly in safeguarding life (ḥifẓ al-nafs) and wealth (ḥifẓ al-māl). The system not only provides financial protection but also embodies spiritual and social dimensions through the principles of ta‘āwun (mutual assistance), ‘adālah (justice), and maslahah (public welfare). Therefore, Islamic insurance can be viewed as a financial instrument that integrates economic benefit with ethical and social well-being in alignment with the ultimate objectives of maqāṣid al-syarī‘ah.